Does E-commerce adoption create SME performance: A Literature Review - Ali Hanafiah; Kemal Sandi; Asri Nur Aina (International Journal of Artificial Intelligence Research, 2022)
This study aims to examine previous research in order to determine the effect of technology and organization on SME performance mediated by E-commerce adoption. This study applies various theories, namely the theory of diffusion of innovation (DOI), and technology, organization, environment (TOE) to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework about SME performance in the perspective of the two theories. This article is important for management and further research considering that not many previous studies have used the theoretical framework of diffusion of innovation (DOI), and technology, organization, environment (TOE) to test a similar research model. This study has limitations in obtaining research that examines the company's environment from the perspective of technology, organization, environment (TOE) theory. Nevertheless, this study carries a new framework that illustrates the contribution of technology, organization, and E-commerce adoption to SME performance.